PELATIHAN DAN PENDAMPINGAN PEMBUKUAN SEDERHANA PADA PABRIK KERUPUK - Verliana, Dea; Lesti, Aulia Thasabita; Herawati, Helmi; Chelomitha, Imellia; Saputra, Aris Dwi (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The aim of this article is to explore training and assistance in simple bookkeeping at a cracker factory. The research method used is qualitative using a case study approach. Data is collected through in-depth interviews, observation, participation and field analysis. The results of the article show that training and bookkeeping assistance at the cracker factory plays an important role in efforts to increase profitsband losses at the factory, as well as identifying and overcoming factory problems that underlie the losses.The conclusion of this article shows that training and mentoring in cracker factories can be an important tool in increasing the effectiveness of cracker factories.